2006
DOI: 10.1038/sj.bjc.6603001
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, steroid receptors and clinical/pathological response in breast cancer treated with letrozole

Abstract: Sixty-three postmenopausal women with large primary breast cancers were treated with neoadjuvant letrozole (2.5 mg daily) for 3 months. Tumour samples were taken at diagnosis and after 10–14 days and 3 months treatment. Immunohistochemical staining for Ki67, oestrogen receptor (ER) and progesterone receptor (PgR) was performed and related to clinical (ClinR) and pathological responses (PathR) after 3 months treatment. ClinR was observed in 48 of 63 cases (76.2%) and PathR in 47 of 62 (75.8%). Pretreatment Ki67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 20 publications
12
73
0
Order By: Relevance
“…This is consistent with our previous report that the expression of steroid receptors (and their change with treatment) did not differ significantly between responding and nonresponding tumors. 28 Similar observations apply to changes in proliferation indices that occur more frequently than clinical response. We reported this previously with regard to immunohistochemical staining for Ki67 28 but now demonstrate the same phenomenon with regard to RNA expression of other markers of proliferation in the same tumor population.…”
Section: Clinical Response and Resistancementioning
confidence: 72%
“…This is consistent with our previous report that the expression of steroid receptors (and their change with treatment) did not differ significantly between responding and nonresponding tumors. 28 Similar observations apply to changes in proliferation indices that occur more frequently than clinical response. We reported this previously with regard to immunohistochemical staining for Ki67 28 but now demonstrate the same phenomenon with regard to RNA expression of other markers of proliferation in the same tumor population.…”
Section: Clinical Response and Resistancementioning
confidence: 72%
“…ER, progesterone receptor (PR), HER-2/neu, Ki67 and the oestrogen-regulated gene pS2 were analysed using standard immunohistochemical methods as already published (Geisler et al, 2001;Miller et al, 2006). ER and PR were reported as percentage of positively stained cells and the tumours were considered positive if X10% of the cells stained for ER/PR (B), or as Allred score (E) where the first number represents an estimation of ER-or PR-positive tumour cells (0, none; 1, o1%; 2, 1 -10%; 3, 10 -33%; 4, 33 -66% and 5, 466%) and the second number represents the average intensity of ER-or PR-positive tumours cells (0, none; 1, weak; 2, intermediate and 3, strong) (Harvey et al, 1999).…”
Section: Tissue Oestrogen Measurements and Histochemical Methodsmentioning
confidence: 99%
“…This material was collected in three similar protocols performed in Bergen, Norway (B) and Edinburgh, UK (E) as previously reported (Geisler et al, 2001(Geisler et al, , 2008Miller et al, 2006). In summary, a total of 31 breast cancer patients treated with a non-steroidal AI (anastrozole or letrozole) as primary medical treatment (previously termed neo-adjuvant therapy) were enrolled.…”
Section: Study Populationmentioning
confidence: 99%
“…We further observed a down-regulation of PR expression levels in all therapy groups. A decrease of PR during neoadjuvant therapy with aromatase inhibitors but also during an anthracycline-based chemotherapy is also known from the literature (15,16,(21)(22)(23)31). Therefore, a re-evaluation of ER· and PR status after PST is strongly recommended in order to optimize individual therapy decisions based on the actual receptor expression.…”
Section: Variations Of Oestrogen Receptor · and Progesterone Receptormentioning
confidence: 99%
“…Several research groups observed significant changes in expression levels of tumour parameters like ER·, PR or Her-2 during PST (15)(16)(17)(18)(19)(20)(21)(22)(23). Therefore, it is strongly recommended that hormone receptor expression and other biological markers should be re-evaluated after PST in order to make sure that post-surgery treatment is tailored adequately.…”
Section: Introductionmentioning
confidence: 99%